International migrations and ethnic interactions in the modern world: features of social actualization - M. A. Yuzhanin (Путеводитель предпринимателя, 2020)
The presented article researches the features of the social implementation of the processes of international migration and ethnic interactions in the modern world. The author consistently focuses on the analysis of statistical data, driving forces and factors of international migration movements affecting the globalizing planetary society in general and Russia in particular. A special place in the study is paid to the problems of sociocultural adaptation in the context of interethnic relations, the formation of various behavioral models and strategies of interaction between representatives of different peoples and cultures of the world, as well as topical issues of the development and practical implementation of an effective integration policy of the state in relation to the multiethnic and multicultural contingent of its population. The materials of this article are intended to contribute to both scientific understanding and practical achievement of harmonization of ethnic and cross–cultural interactions at various levels of public life’s organization.